Systemic Misalignment in Foreign Language Teaching in Algeria: A Critical Review of Policy, Curriculum, and Pedagogy - Khansaa Mohammed Cherif (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
Foreign language teaching in Algeria operates within a stratified multilingual ecology shaped by Arabic, French, Tamazight, and the growing prominence of English. While existing scholarships have examined language policy, curriculum, and pedagogy as separate domains, limited attention has been paid to their dynamic interrelations. This study aims to critically examine how these dimensions interact within the Algerian educational system. Methodologically, the study adopts a critical integrative literature review, synthesizing recent research on language policy, curriculum design, and pedagogical practices in Algeria. The analysis identifies a systemic condition of misalignment across these domains: policy frameworks generate competing linguistic priorities, curricula reflect hybrid and unevenly implemented models, and pedagogical practices adapt to multilingual classroom realities. The findings suggest that challenges in foreign language education are not merely pedagogical but structurally embedded within the broader sociolinguistic and institutional context. The study proposes “systemic misalignment” as an analytical framework for understanding multilingual education in postcolonial settings. It concludes that more coherent and context-responsive approaches are needed to better align policy, curriculum, and pedagogy. The study also contributes to ongoing debates in applied linguistics by offering a multi-level perspective on language education in multilingual environments. Keywords: foreign language education; language policy; multilingual education; curriculum design; pedagogy; systemic misalignment; Algeria